2014
DOI: 10.1186/1471-2458-14-829
|View full text |Cite
|
Sign up to set email alerts
|

Association of lifestyle habits and academic achievement in Norwegian adolescents: a cross-sectional study

Abstract: BackgroundWhile healthy lifestyle habits are generally assumed to be important for high academic achievement, there has been little research on this topic among adolescents. The aim of this study was therefore to examine the associations between several lifestyle habits and academic achievement in adolescent girls and boys.MethodsThe study included 2,432 Norwegian adolescents, 15–17 years old. A self-report questionnaire was used to assess dietary-, physical activity-, smoking- and snuffing habits and academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
121
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 29 publications
11
121
1
9
Order By: Relevance
“…Since economic considerations are probably of the main concern in big families, they preferred transitional to healthy diet which contains more expensive components such as meat, dairy products and nuts. School performance score was positively correlated to healthy DP; it means that students with healthy dietary habits had better school performance and subsequently higher scores, which was consistent with other studies (20)(21)(22).…”
Section: Discussionsupporting
confidence: 80%
“…Since economic considerations are probably of the main concern in big families, they preferred transitional to healthy diet which contains more expensive components such as meat, dairy products and nuts. School performance score was positively correlated to healthy DP; it means that students with healthy dietary habits had better school performance and subsequently higher scores, which was consistent with other studies (20)(21)(22).…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies revealed that breakfast consumption is highly associated with nutrition adequacy among children and adolescents [5,9,10]. The results of the current study provide evidence for the association between breakfast consumption and the academic performance of high school students in Abu Dhabi.…”
Section: Discussionsupporting
confidence: 62%
“…It found that the regular consumption of breakfast as well as increased intake of healthy foods are associated with increased learning outcomes and high school achievements, particularly in female students [10].…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be explained in part by the criteria for classifying breakfast skipping. Some studies have assessed frequency groups of breakfast consumption [5,11,32,[35][36][37], while others are based on 24-hour recall [7,26], and still others classified as daily or not daily consumption [38,39], as in this study. This criterion was used because it had the best discriminatory power in this population, and because higher frequency of breakfast consumption is desirable, as it has protective effects, particularly against obesity [15,37].…”
Section: Discussionmentioning
confidence: 99%